Two years COVID-19 pandemic: Development of university students' mental health 2020–2022 - Kohls, Elisabeth; Guenthner, Lukas; Baldofski, Sabrina; Brock, Tanja; Schuhr, Jan; Rummel-Kluge, Christine (Frontiers in Psychiatry, 2023)
The literature indicates a negative impact on the mental health of university students during the COVID-19 pandemic. It remains unclear if this negative impact persists even after lockdown measures are lifted. The current study therefore investigates the mental health status of students by drawing on two previous studies the present study seeks to investigate differences in the mental health status across three time points. More than one third of students exhibited clinically relevant symptoms of depression (35.5%), hazardous alcohol use (33.0-35.5% depending on gender) or anxiety disorder (31.1%). Taken together, almost two out of three (61.4%) students reported clinically relevant symptoms in at least one of the aforementioned symptom patterns, while almost one fifth of students reported suicidal ideation or thoughts of self-harm (19.6%). Higher perceived stress and loneliness significantly predicted higher levels of depressive symptoms, while resilience and social support were identified as protective factors. Compared to 2020 and 2021, levels of depressive symptoms were significantly reduced in 2022 when compared to 2021, levels of hazardous alcohol consumption showed a small but significant increase from 2021 to 2022. Worryingly, prevalence of suicidal ideation was the highest yet, being significantly higher than in 2020 (14.5%) and 2021 (16.5%). These results confirm previous results that the pandemic had and still has a negative impact on the mental health of university students. The present study broadens this view by the fact that some areas seem to recover quicker, while others seem to increase worryingly. Especially the persistent rise in suicidal ideation from 2020 to 2021 and to 2022, a constant reduction in reported social support and associated perceived loneliness is concerning. The claim for low-threshold and accessible mental health support for university students remains the same as in the beginning of the pandemic.